2017
DOI: 10.1158/1055-9965.epi-16-0776
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy and Risk of Prostate Cancer in a Screening Trial

Abstract: Vasectomy has been implicated as a risk factor for prostate cancer in multiple epidemiologic studies over the past 25 years. Whether this relationship is causal remains unclear. This study examines the association between vasectomy and prostate cancer in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, which randomized men to usual care or annual prostate cancer screening. We performed a retrospective analysis of 13-year screening and outcomes data from the PLCO trial. Multivariable Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Vasectomy has been discussed as a putative risk factor for PCa development over recent decades, and some studies have supported an association with lethal PCa [100]. On the contrary, most recent studies found either no or only a weak association between vasectomy and overall PCa risk (closer to the null with increasingly robust study design) and no significant association with HGPCA, advanced-stage PCa, or fatal PCa, finally resulting in currently strong evidence rebutting a relationship between vasectomy and PCa [101][102][103][104][105].…”
Section: Sexual Activity and Risk Of Pcamentioning
confidence: 99%
“…Vasectomy has been discussed as a putative risk factor for PCa development over recent decades, and some studies have supported an association with lethal PCa [100]. On the contrary, most recent studies found either no or only a weak association between vasectomy and overall PCa risk (closer to the null with increasingly robust study design) and no significant association with HGPCA, advanced-stage PCa, or fatal PCa, finally resulting in currently strong evidence rebutting a relationship between vasectomy and PCa [101][102][103][104][105].…”
Section: Sexual Activity and Risk Of Pcamentioning
confidence: 99%
“…In our Health Professionals Follow-up Study (HPFS) [6], tightly controlling for confounding by restricting to a highly screened subcohort attenuated the relative risk and 95% confidence interval (RR 1.05, 0.94-1.17) compared to a simpler adjustment (RR 1.10, 1.04-1.17). Within the PLCO screening trial, the relative risk for vasectomy and prostate cancer was 1.11 (1.03-1.20) in the usual care arm compared to 1.03 (0.95-1.11) in the screening arm, minimally affected by confounding [7]. To our knowledge, no other individual study in the meta-analysis investigated screening's impact to such depth.…”
mentioning
confidence: 90%
“…A total of 466 unique records were identified. Of these, 70 full-text articles were assessed for eligibility and 37 met the inclusion criteria for qualitative and quantitative analysis [4] , [6] , [7] , [8] , [9] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] . The reasons for exclusion are summarized in Figure 1 .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…These discrepancies are due to the paucity of documented causal associations, and possible detection biases related to PCa screening and closer follow-up among vasectomy patients, and modest clinical significance with a relative risk very often close to 1. Recently, several large, high-quality reports demonstrated conflicting results [5] , [6] , [7] , [8] , [9] . A recent meta-analysis that included the most recent reports found that vasectomy was associated with localized and advanced PCa [10] .…”
Section: Introductionmentioning
confidence: 99%